DEWAN DIREKSI, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN DAN NILAI PERUSAHAAN - Alfatah, Zafar Shidiq; Nurlaela, Siti; Dewi, Riana R (Jurnal Investasi, 2020)
The development of the property and real estate business is projected to continue to increase. The visible growth in the number of houses ready for habitation development, apartments, hotels, office buildings, shopping centers and so on. This study aims to examine and analyze the influence of the board of directors, managerial ownership, institutional ownership, company size on the value of companies property and real estate listed on the Indonesia Stock Exchange (IDX) in 2013-2018. The population in this study are all companies property and real estate listed on the Indonesia Stock Exchange (IDX) in 2013-2018, amounting to 48 companies. The sample selection in this study uses purposive sampling so that 12 companies can be obtained during 6 observation periods. The method of data analysis uses multiple linear regression analysis. The results showed the board of directors had no effect on the value of companies property and real estate listed on the Indonesia Stock Exchange (IDX) in 2013-2018. While managerial ownership, institutional ownership, company size affect the value of companies property and real estate listed on the Indonesia Stock Exchange (IDX) in 2013-2018. This research is expected to be useful information for companies to encourage company performance in increasing company value.